Apigenin protects mice against 3, 5-diethoxycarbonyl-1, 4-dihydrocollidine-induced cholestasis. Issue 5 (23rd February 2021) - Zheng, Shihong; Cao, Peichang; Yin, Zequn; Wang, Xuerui; Chen, Yuanli; Yu, Maoyun; Xu, Baocai; Liao, Chenzhong; Duan, Yajun; Zhang, Shuang; Han, Jihong; Yang, Xiaoxiao
Abstract : Apigenin prevented the DDC-induced abnormal lipid metabolism, liver damage and liver fibrosis by reducing inflammation and oxidative stress. Apigenin might be a potential drug for the treatment of cholestatic liver diseases. Abstract : Cholestasis can induce liver fibrosis and cirrhosis. Apigenin has anti-oxidant and anti-inflammatory effects. Herein, we determined whether apigenin can protect mice against cholestasis. In vitro, apigenin protected TFK-1 cells (a human bile duct cancer cell line) against H2 O2 -induced ROS generation and inhibited transforming growth factor-β-activated collagen type 1 alpha 1 and α-smooth muscle actin in LX2 cells (a human hepatic stellate cell line). In vivo, cholestatic mice induced by 3, 5-diethoxycarbonyl-1, 4-dihydrocollidine (DDC) were treated with apigenin. Apigenin potently blocked DDC-induced gallbladder atrophy and associated liver injury, fibrosis and collagen accumulation. Moreover, apigenin relieved the DDC-caused abnormality of bile acid metabolism and restored the balance between bile secretion and excretion by regulating the farnesoid X receptor signaling pathway. Furthermore, apigenin reduced inflammation or oxidative stress in the liver by blocking the DDC-activated Toll-like receptor 4, nuclear factor κB and tumor necrosis factor α, or DDC-suppressed superoxidase dismutase 1/2, catalase and glutathione peroxidase. Taken together, apigenin improves DDC-induced cholestasis by reducing inflammation and oxidative damage and improving bile acid metabolism, indicating its potential application for cholestasis treatment.